Water Discharge Control in BLDC Motor Driven Pumps to Increase Drip Irrigation Accuracy - suwito suwito; Muhammad Rivai (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
Drip irrigation is the most energy and water-efficient irrigation. The multi-sector drip irrigation system can irrigate various types of plants which are divided into several sectors. Changes in the number of active sectors due to differences in irrigation duration resulted in unstable emitter discharges. This instability makes irrigation inaccurate and results in excess or shortage of water supply for crops. Water pump control is needed to match the amount of active emitter discharge. This study controls the discharge of water pumps in multi-sector drip irrigation so that the discharge is in accordance with the number of active emitters. The pump discharge control uses the proportional integral and derivative (PID) method. The type of centrifugal water pump used is driven by a Brushless DC (BLDC) motor with a six-step speed control method. The test results show that the pump can adjust the water discharge with a steady state error of 2.8%.